Teori Kultivasi: Analisis Teori Penyuburan Karya Melvin L. Defleur dan Sandra J. Ball-Rokeach dalam Bukunya Theories of Mass Communication Tahun 1988 dan Aplikasinya dalam Pengembangan Anak Usia Dini - Yusri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This article discusses other media impact cultivation theories such as silence spiral theory, media framing theory, and social learning theory. This discussion looks more at the important components of this discussion of the theory of scattering in the book Theories of Mass Communication by Malvin L. Defleur and Sandra J. Ball-Rokeach. According to the theory of cultivation, television messages affect the behavior of individuals. The effect of a stirring between a heavy television viewer and a light viewer. The findings of this study, taken in combination with previous studies, seem to suggest that in a world the capitalist value of television can pay greater attention than democratic values.